Acetaminophen and acetylcysteine dose and duration: Past, present and future - Rumack, Barry H; Bateman, D Nicholas (Clinical toxicology (Philadelphia, Pa.), 2012)
Abstract Acetylcysteine has been utilized successfully in the treatment of acetaminophen overdose since the 1970s. Although prospective trials as to efficacy and safety of acetylcysteine were conducted, there were no randomized controlled trials. This commentary addresses the reasons for this, and the background to choice of dose of acetylcysteine utilized in the oral and IV dosing regimens. Nomograms to predict possible hepatotoxicity based upon time of ingestion of acetaminophen were developed from a relatively arbitrary definition of toxicity as an aspartate aminotransferase/alanine aminotransferase (ALT/AST) greater than 1000 IU/L. While these have proved generally useful, patients still continue to develop hepatic damage after acetaminophen overdose, particularly if they present late after ingestion. The optimum management of these patients remains unclear, and one area of uncertainty is the dose and duration of acetylcysteine in various circumstances. This article discusses the issues that need to be elucidated to better target changes in acetylcysteine dose. The potential for measurements of other markers to improve treatment selection is the subject of further research.